Effect of irrigation regime on the production of volatiles that affect the aroma of the pear variety Triumph of Vienna (Pyrus communis L.) (2019)
Water is a major component of plants that directly and indirectly affects physiological processes. One of the consequences of a hydric deficit in the pear fruit is modification of the aroma. No information exists on the effect of a water deficit on the sensory profile and volatile composition of this species. The objective was to determine the production of volatiles in the harvest and post-harvest of pear var. Triumph of Vienna (Pyrus communis L.) with regulated deficit irrigation (RDI). The irrigation treatments consisted of the application of water regimes that were 100 (Control), 74 and 48% of the ETc during the rapid fruit growth period. The rest of the season plants were irrigated at 100%ETc. In the deficit treatments, there were no significant reductions with respect to the control in the quality of the fruits, obtaining a water savings in 74 and 48%ETc of 26 and 40%, respectively. The esters were the volatile compounds that contribute greatly to aroma, which increased steadily during the climacteric phase. Under the limited water conditions, watering with regulated, deficit doses obtained production that was similar to that of well-watered crops, provided that it was carried out in the phenological stage of low sensitivity and that the tolerance limits of stress were not exceeded.